The Effect of Berberan Exercise Using Resistance Bands on Sickle Kick Ability - Aprilialdasari, Nabilah; Fardi, Adnan; Suwirman, Suwirman; Oktavianus, Irfan (Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2023)
Background and aim. This study observes that the ability to perform sickle kicks is still not optimal. Therefore, this study aims to determine the effect of weight training using black Resistance Bands Tube Sets on the sickle kick ability of Putera Muhammadiyah Pencak Silat Tapak Suci athletes at PGRI University, West Sumatra.Methods. This type of research is pre-experiment. Samples were taken using a purposive sampling technique with a sample of 14 young and adult female athletes from Tapak Suci, PGRI University, West Sumatra. The analysis used is the sample dependent t test. The instruments and data collection techniques used in the research were in the form of a crescent kick speed test.Results. The results showed that there was a significant effect of weight training using resistance bands seen from: (a) the average ability to kick on the right leg during the pre-test was 20 kicks and after being given treatment the average athlete performed 21 kicks in the post-test, indicating an increase of 1 kick, with tcount 5.551 > ttable = 1.771; and (b) the athlete's left foot kick increased by an average of 1 kick, from 18 kicks in the pre-test to 19 kicks in the post-test. This is proven after the